Srategi Pelaku Usaha Kayu Harwood Dalam Menjaga Kualitas Produk Dan Meningkatkan Daya Saing ekspor - Moh Nurhedi; Moh. Fakhri Siddiqi (Universitas Persada Indonesia YAI, 2026)
The increasingly fierce competition in the wood industry requires hardwood businesses to maintain product quality and increase export competitiveness. This study aims to determine the strategies of business owners in maintaining product quality and increasing export competitiveness in Margoayu Village, Pakuniran District. This study used a descriptive qualitative method. Data were obtained through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The results show that business owners maintain product quality through raw material selection, production process control, wood drying, and product finishing. Constraints faced include limited technology, capital, and market access. Efforts to increase competitiveness are carried out through improving product quality and marketing development. Conclusion This study shows that product quality is a major factor in increasing hardwood export competitiveness, thus requiring improvements in product quality, production technology, and marketing strategies.